Benzoquinonoid-bridged dinuclear actinide complexes. Issue 35 (23rd August 2017) - Hohloch, Stephan; Pankhurst, James R.; Jaekel, Esther E.; Parker, Bernard F.; Lussier, Daniel J.; Garner, Mary E.; Booth, Corwin H.; Love, Jason B.; Arnold, John
Abstract : We report the coordination chemistry of benzoquinonoid-bridged dinluclear thorium(iv ) and uranium(iv ) complexes with the tripodal ligand tris[2-amido(2-pyridyl)ethyl]amine ligand, L . Abstract : We report the coordination chemistry of the tripodal tris[2-amido(2-pyridyl)ethyl]amine ligand, L, with thorium(iv ) and uranium(iv ). Using a salt-metathesis strategy from the potassium salt of this ligand, K3 L, new actinide complexes were isolated, namely the dimeric thorium complex [ThCl(L)]2 (1 ) and the monomeric uranium complex UI(THF)(L) (2 ); under different crystallisation conditions, the dimeric uranium complex is also isolated, [UI(L)]2 (2-dimer ). With the aim of studying electronic phenomena such as magnetic exchange between two actinide ions, we have synthesised the first examples of dinuclear, quinoid-bridged actinide complexes from dianionic 2, 5-bis[2, 6-(diisopropyl)anilide]-1, 4-benzoquinone (Q Dipp ) and 2, 5-bis[2-(methoxy)anilide]-1, 4-benzoquinone (Q OMe ) ligands. The resulting complexes are [Th(L)]2 Q Dipp (3 ), [Th(THF)(L)]2 Q OMe (5 ) and [U(L)]2 Q OMe (6 ). The targeted [U(L)]2 Q Dipp complex (4 ) could not be isolated. All isolated complexes have been characterised by spectroscopic methods and X-ray crystallography. The uranium(iv ) complexes2-dimer and6 have been studied by SQUID magnetometry but indicate that there is negligible magnetic exchange between the two uranium(iv ) ions. The reduced form of6, [K(18-c-6)][6 − ] is unstable and highly sensitive, but X-ray crystallography indicates that it is a novel U IV U IV complex bridged by a quinoid-radical.